Jaw musculature of the Meiglyptini (Aves: Piciformes: Picidae) - Donatelli, Reginaldo José [UNESP] (Wiley, 2012)
The Meiglyptini comprise eight species of woodpeckers grouped into three genera, two of which contain three species ( Meiglyptes and Mulleripicus), while one genus includes two species ( Hemicircus). The purpose of this study is to describe the mandibular apparatus found in six species of Meiglyptini and to compare them with each other and with other woodpecker species. The results reveal a number of structures that are worth mentioning: (i) the components of the external mandibular adductor system of Hemicircus concretus, particularly the M. adductor mandibulae externus caudalis medialis, are underdeveloped compared with the other investigated species; (ii) the muscles of the internal mandibular system are structurally different among Meiglyptes species and are less developed, both in size and in structure, in H. concretus; (iii) the M protractor quadrati is vestigial in Meiglyptes species; (iv) the muscles of the protractor system of the quadrate are relatively undeveloped in H. concretus; (v) most of the muscles of the pterygoideus system are structurally differentiated in Meiglyptes species. It appears that the complexity of the mandibular apparatus is associated with the type of food consumed, as the apparatus of the frugivorous species H. concretus is markedly different from that of the insectivorous species. © 2012 The Royal Swedish Academy of Sciences.
Keywords: Birds; Mandibular apparatus; Meiglyptini; Picidae